Analysis of TPACK Integration in the Preparation of Teaching Modules for Prospective Mathematics Education Teachers at the Islamic University of Riau - Wulandari, Tria; Rezeki, Sri (FKIP - Universitas Riau, 2025)
This study aims to describe the ability to integrate TPACK (Technological Pedagogical And Content Knowledge) in the preparation of teaching modules for prospective mathematics education teachers. This type of research is quantitative descriptive. The data collection technique used is observation in the form of documentation studies of 41 teaching modules made by prospective mathematics education teachers at UIR in the microteaching course and using interview techniques to find out more about students' knowledge. The data used in the study is the ability to integrate technology in the TPACK of prospective teachers which includes TK (Technological Knowledge), PK (Pedagogical Knowledge), CK (Content Knowledge), TPK (Technological Pedagogical Knowledge), TCK (Technological Content Knowledge), PCK (Pedagogical Content Knowledge), and TPACK (Technological Pedagogical Content knowledge). This study uses quantitative data analysis techniques, namely descriptive statistical data analysis. The results of this study indicate that, TK prospective teachers (29.8%) are in the poor category, PK prospective teachers (59%) are in the sufficient category, CK prospective teachers (53.6%) are in the sufficient category, TPK prospective teachers (7.3%) are classified as not good, TCK prospective teachers (4.8%) are in the poor category, PCK prospective teachers (63.4%) are in the good category, and TPACK prospective teachers (19.9%) are classified as not good.